2011
DOI: 10.1007/s10493-011-9467-z
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-dependent development and life table parameters of Typhlodromus bagdasarjani (Phytoseiidae) fed on two-spotted spider mite

Abstract: The predatory mite Typhlodromus bagdasarjani Wainstein and Arutunjan (Acari: Phytoseiidae) is an indigenous and widespread species of the Middle East fauna. In this paper we assess the effect of temperature on developmental rate and reproduction potential of T. bagdasarjani under laboratory conditions. The development of this species was determined at 15, 20, 25, 30, 35 and 37.5 ± 1°C, 60 ± 10% RH and L16:D8 h photoperiod. The total developmental time averaged 28.2, 15.0, 8.9, 7.6, 7.2 and 7.4 days at 15-37.5°… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
15
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(19 citation statements)
references
References 37 publications
4
15
0
Order By: Relevance
“…These results are consistent with other life history parameters summarized for phytoseiid mites (Genini et al 1991;Gotoh et al 2004;Broufas et al 2007;Ganjisaffar et al 2011;Lee and Gillespie 2011). Duration of mite development in this study was similar to rates found for the European strain of T. pyri at temperatures from 20 to 30°C (Genini et al 1991).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…These results are consistent with other life history parameters summarized for phytoseiid mites (Genini et al 1991;Gotoh et al 2004;Broufas et al 2007;Ganjisaffar et al 2011;Lee and Gillespie 2011). Duration of mite development in this study was similar to rates found for the European strain of T. pyri at temperatures from 20 to 30°C (Genini et al 1991).…”
Section: Discussionsupporting
confidence: 91%
“…It is possible that over-estimation of T. pyri developmental thresholds may have occurred because development was not observed at the lowest (12.5°C) or highest (35°C) temperatures assayed. The minimal threshold values were, however, within 3°C degrees of those reported for T. pyri and other related phytoseiid species (Genini et al 1991;Gotoh et al 2004 and references therein, Ganjisaffar et al 2011). In addition, the non-linear model used in this study provided the best fit to the current data as similarly reported by Ganjisaffar et al (2011) and Lee and Gillespie (2011).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Our results showed that high temperature (37°C) caused a decrease in developmental rate from a linear trend; therefore, for predicting the developmental rate and estimating the suitable values of the critical thresholds ( T min , T opt and T max ) of N. barkeri at a temperature range of 15 to 37°C, application of nonlinear models is necessary. Similar results were also reported for other predatory mites (Broufas & Koveos, 2001; Broufas et al ., 2007; Ganjisaffar et al ., 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Assuming that development is a linear function of the temperature range of 15–35°C, the lower temperature threshold (12.07°C) and thermal constant (86.20 DD) were estimated by the linear model for total development of N. barkeri , in which this thermal constant is close to that reported for Amblyseius californicus McGregor (90.0 DD) (Castagnoli & Simoni, 1999), Euseius finlandicus (Oudemans) (93.45 DD) (Broufas & Koveos, 2001) and Amblyseius longispinosus (Evans) (80.5 DD) (Nakagawa, 1984). The obtained thermal constant is lower than that reported for Phytoseius plumifer (Canestrini and Fanzago) (125.3 DD) (Kouhjani‐Gorji et al ., 2008) and Typhlodromus bagdasarjani Wainstein and Arutunjan (162 DD) (Ganjisaffar et al ., 2011). Conversely, this thermal constant for N. barkeri is higher than that reported for Phytoseiulus longipes Evans (28.7 DD) (Ferrero et al ., 2007) and A. californicus (59.2 DD) (Gotoh et al ., 2004).…”
Section: Discussionmentioning
confidence: 99%